Ophthalmological and electrophysiological features of Parkinson’s disease - Nowacka, Barbara; Lubiński, Wojciech; Karczewicz, Danuta (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: Based on available literature, the authors describe the most frequent ocular diseases and symptoms, as well as bioelectrical dysfunction of the visual pathway in patients with Parkinson’s disease (PD). Material and methods: Data published in literature available in PubMed library. The most often ocular diseases, symptoms and the bioelectrical dysfunction were diagnosed using routine ophthalmological examination including tear film tests, perimetry, optical coherence tomography (OCT), color and contrast sensitivity tests, and electrophysiological recordings like EOGs, flash, pattern and multifocal ERGs, VEPs. Results: The most frequent ocular diseases in PD are dry eye syndrome and glaucoma. At least 25% of PD patients manifest visual hallucinations. The most prominent bioelectrical dysfunction of the visual pathway was observed in outer layers of the retina (retinal pigmented epithelium, photoreceptors) and it was registered mainly in EOG, PERG and mfERG tests. Conclusions: During examination of PD patents, general ophthalmologists should especially pay attention to diagnosis and treatment of glaucoma and dry eye syndrome. In PD visual deficits may occur without any noticeable changes in the routine ophthalmological examination. Electrophysiological recordings can explain, at least partially, visual dysfunction in course of PD.